2018
DOI: 10.1002/adma.201707390
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Dependent Processes Measured without a Permanent Magnet

Abstract: A novel Hall circuit design that can be incorporated into a working electrode, which is used to probe spin-selective charge transfer and charge displacement processes, is reviewed herein. The general design of a Hall circuit based on a semiconductor heterostructure, which forms a shallow 2D electron gas and is used as an electrode, is described. Three different types of spin-selective processes have been studied with this device in the past: i) photoinduced charge exchange between quantum dots and the working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…The other electrons (or holes) with the opposite spin are backscattered at source electrode decreasing I D by half. Although CISS effect appears detrimental for charge transport, it offers a wealth of new opportunities of which the development of spintronics with no magnets is not the least …”
Section: Charge Transportmentioning
confidence: 99%
“…The other electrons (or holes) with the opposite spin are backscattered at source electrode decreasing I D by half. Although CISS effect appears detrimental for charge transport, it offers a wealth of new opportunities of which the development of spintronics with no magnets is not the least …”
Section: Charge Transportmentioning
confidence: 99%
“…The CISS can accumulate spins in non-magnetic layers that behaves like magnets in which the accumulated spins can be detected by Hall devices 24 . For example, when the Hall bar that is made of two-dimensional electron gas (2DEG) covered by chiral molecules/nanoparticle assembly is exposed to a circularly polarized light, the measured Hall voltage reveals striking contrasts depending on both the handedness of chiral molecules and the sign of circular polarization of the light.…”
mentioning
confidence: 99%
“…When x-and y-polarized plane waves are incident, due to the existence of polarization conversion, we obtain the following reflection coefficients of linearly polarized light: r xx , r yx , r yy and r xy . Then, the reflection coefficient of CPL can be obtained by Equation (1). Here, x, y, r and l in the subscript represent x-polarized light, y-polarized light, right-handed circularly polarized light and left-handed circularly polarized light, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the organic world, there are many chiral molecules, such as protein, DNA, sugar molecules, viruses, amino acids and liquid crystals, but there are few chiral structures in nature. Later, it is found that chiral materials can control the spin of electrons to a certain extent [1][2][3]. In addition, thanks to the development of metamaterials, the control of the spin of photons has been realized [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%